2012
DOI: 10.4314/ahs.v12i2.11
|View full text |Cite
|
Sign up to set email alerts
|

Ecalmpsia: maternal and fetal outcome

Abstract: Objective: To determine the incidence of eclampsia and examine the maternal and fetal outcome. Methods: A hundred and twenty consecutive admissions with eclampsia managed in Aminu Kano Teaching Hospital, Kano, Nigeria, were prospectively collated and analysed. Maternal and fetal morbidity and mortality were recorded. Results: The incidence of eclampsia was 1.2% of deliveries. Most (69.2%) of the patients had no antenatal care. In 93 (77.5%), the convulsions were controlled with diazepam, and 22.5% magnesium su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
23
1
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 17 publications
6
23
1
1
Order By: Relevance
“…This is consistent with the findings in other centres in Nigeria [7,9,10,12,13] where lack of quality antenatal care is identified in most patients with eclampsia. Reducing recognised obstacles to antenatal care attendance have been shown to favour the uptake of antenatal and maternity care, with positive impact on morbidity and mortality, including eclampsia.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…This is consistent with the findings in other centres in Nigeria [7,9,10,12,13] where lack of quality antenatal care is identified in most patients with eclampsia. Reducing recognised obstacles to antenatal care attendance have been shown to favour the uptake of antenatal and maternity care, with positive impact on morbidity and mortality, including eclampsia.…”
Section: Discussionsupporting
confidence: 82%
“…The incidence in the study population was 0.84% is similar to 0.80% reported in Aba [11] but is lower than that the 5.7% reported in Nguru [9], 4.29% in Sokoto [8], 2.52% in Irrua [12], 1.3% in Benin [20], 1.2% in Kano [7] and 0.91% in Nnewi [10] and Ile-Ife [13] respectively. The mean age of eclamptic women in the study 26.9 years was similar to the reports from Benin [20], Nnewi [10] and Aba [12] where eclampsia occurred mostly in the 25-29 year group.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…21,22 In our study most of the cases developed ante partum eclampsia (80.8%) before 37 weeks of gestation (70%) similar to other Indian studies and study conducted in Nigeria by Jido TA, whereas in the UK, 44% of eclampsia were postpartum and had lower incidence of ante partum eclampsia which could be due to good ANC surveillance. [8][9][10]14,19 The present study showed 3+ and 4+ urine albumin by dipstick test in most of the eclamptic patients (65.2% and 26.8%) correlating with poor maternal and perinatal outcome. 12,19,20 In the present study, most of the eclamptic patients (82%) were delivered by vaginal route similar to other Indian studies due to lack of facilities for intensive care in our institute but in recent years as well as in developed countries caesarean section has been opted for the preferred mode of delivery.…”
Section: Discussionmentioning
confidence: 99%
“…[8][9][10][11] This incidence is higher than other developing countries also. [12][13][14][15] The incidence of eclampsia in developed countries is estimated to about 5-7/10,000 deliveries whereas in developing countries varies widely 1 case/100 to 1 case/1700 pregnancies. 5,16,17 Majority of the patients are of primigravida (78.8%) in their early reproductive age <25 years (60.4%) with unsupervised pregnancy ( in their antenatal period and referred cases (76.8%).…”
Section: Discussionmentioning
confidence: 99%